Designing a voltage control system of the magnetoelectric generator with magnetic flux shunting for electric power systems - Ostroverkhov, Mykola; Chumack, Vadim; Tymoshchuk, Oksana; Kovalenko, Mykhailo; Ihnatiuk, Yevhen (Eastern-European Journal of Enterprise Technologies, 2022)
The object of research in this work is a three-phase magnetoelectric generator with magnetic flux shunting based on industrial induction electric motors. The presence of a magnetic shunt makes it possible to control the voltage of the generator by changing the excitation current in the non-contact electrical winding of the magnetic shunt, which is powered by direct current. Thus, the problem of stabilization of the output voltage of the generator with permanent magnets is solved when the speed of rotation and load change. This paper reports the construction of a three-dimensional field mathematical model of the generator, which allows for electromagnetic calculations of the generator with specified parameters, taking into consideration the influence of final effects, magnetic scattering fields, as well as their radial-axial nature. The results of the calculation of the electromagnetic field are the initial parameters for building a simulation model in the MATLAB-Simulink environment. A simulation model of a magnetoelectric generator with magnetic flux shunting under conditions of changing rotational speed and load has been constructed in the MATLAB-Simulink environment. On the basis of the built models, the performance characteristics of a magnetoelectric generator with magnetic flux shunting were established, which show the limits of control of the output voltage. Adjusting characteristics were determined at zero and rated shunt current for different types of load. The adjusting characteristics of the generator are presented at the rated voltage of the generator for different types of load and with an increase to 150 % of the rated value. The study’s results show the high efficiency of the voltage control system of a magnetoelectric generator with a magnetic shunt at different speeds of rotation and load